Wound Care Knowledge, Attitudes, and Practices and Mobile Health Technology Use in the Home Environment: Cross-Sectional Survey of Social Network Users - Kuan, Ya-Ting; Wang, Tze-Fang; Guo, Chao-Yu; Tang, Fu-In; Hou, I-Ching (JMIR Publications, 2020)
BackgroundInjury causing wounds is a frequent event. Inadequate or inappropriate treatment of injuries can threaten individual health. However, little is known about wound care knowledge, attitudes, and practices and mobile health (mHealth) use in the home environment in Taiwan. ObjectiveThis study aimed to evaluate wound care knowledge, attitudes, and practices and mHealth technology use among social network users. MethodsA cross-sectional survey on social media platforms was conducted on adults aged 20 years and older. Data were collected from social network users in the home environment. ResultsA total of 361 participants were enrolled. The mHealth technology use of participants was positively correlated with wound care knowledge (r=.132, P=.01), attitudes (r=.239, P<.001), and practices (r=.132, P=.01). Participants did not have adequate knowledge (correct rate 69.1%) and were unfamiliar with the guidelines of proper wound care (correct rate 74.5%). Most participants had positive attitudes toward wound care and mHealth technology use. A total of 95.6% (345/361) of participants perceived that the use of mHealth technology can improve wound care outcomes, and 93.9% (339/361) perceived that wound care products should be optimized to be used with a mobile device. However, 93.6% (338/361) of participants had no experience using mHealth technology for wound care. ConclusionsOur study shows the potential of mHealth technology to enhance wound care knowledge among social network users. Thus, government agencies and medical institutions in Taiwan should provide easy-to-use information products that enhance wound care knowledge, promote adequate behavior toward wound care, and prevent unpredictable or undesirable outcomes.